The ride [videorecording (DVD)] - Ranarivelo, Alex; Ranarivelo, Alex; Graham, Shane, 1990-; Ludacris (Rapper); Alexander, Sasha, 1973- (Samuel Goldwyn Films, 2021)
Follows the life of BMX racer John Buultjens after he is placed with an interracial foster family and becomes interested in bike riding through lessons from his foster dad.